Occupational headaches: when to suspect? - Santos, Patrick Emanuell Mesquita Sousa; Campelo, Alanny Gabrielly Diogenes; Costa, Ezequiel Gonçalves da; Lima, Guilherme Antonio Morais; Rosado, Matheus Saraiva Valente; Silva-Néto, Raimundo Pereira (Headache Medicine, 2018)
Occupational diseases are directly linked to the worker's profession, while those of work are linked to the work environment. In Brazil, these morbid entities are governed by Law No. 8,213 of July 24, 1991. Occupational headaches were first described by Bernardino Ramazzini in 1700 in his book De morbis artificum diatribe. However, to date, they have not been included in the list of work-related diseases, published by the Ministry of Health, and adopted by the Ministry of Social Security. The classification of Schilling used in occupational diseases in general can be adapted to the diagnoses of occupational headache. To arrive at this diagnosis, three essential elements are necessary: occupational anamnesis, activity diary and causal nexus.